A Rapid Review of Impact Assessment of Climate Change on Health and Mental Well-Being in Africa - Oladimeji, Kelechi Elizabeth; Zungu, Lindiwe; Chocko, Ronnie; Hyera, Francis L.; Nyatela, Athini; Gumede, Siphamandla; Dwarka , Depika; Lalla-Edward , Samanta Tresha (New Voices in Psychology, 2023)
Despite widespread global attention, the potential threats to human health posed by climate change in Africa still need to be further understood. Although there is mounting concern that climate change is a serious risk to human health, less evidence shows a direct causal relationship between climate change and health risks in Africa. In this rapid review, we discuss our synthesis of available evidence on the health implications of climate change with a focus on Africa. PubMed was systematically searched for relevant articles from 2020 to 2023 using a search strategy. Only eligible articles published in the English language with full article access were included for review using the population concept context (PCC) criteria by Joanna Briggs Institute (JBI). After removing duplicates, the selection process began with title and abstract screening, followed by screening full-text articles. Of the 3272 articles retrieved, only 10 were eligible for synthesis. We found mainly reported climate exposures to range from drought, concerning rainfall patterns, and increasing temperatures reported to cause morbidity and mortality through health risks: respiratory diseases, vector-borne diseases, cardiovascular diseases and mental health concerns. Africa still has a huge shortage of available evidence, particularly research focusing on the health implications, including mental health of climate change and interventions to prevent climate change-related health consequences. While the limited global evidence indicates that climate change results in an increased risk to public health, there are gaps in demonstrating the causal links between climate change and societal mental health impacts in Africa. There is also an urgent need for more research on effectively addressing climate hazards that threaten the African continent's public health and well-being.